The Influence Of The Tourism Sector On Regional Financial Performance With Economic Growth As A Mediating Variable In Improving Community Welfare - Nurul WAHYUNI; Mediaty MEDIATY; Syarifuddin RASYID (Journal of Tourism Economics and Policy, 2023)
This study aims to analyze: (1) the influence of the tourism sector on financial performance, (2) the influence of the tourism sector on economic growth, (3) the effect of economic growth on financial performance, (4) the influence of financial performance on people's welfare, (5) the influence of economic growth on financial performance. economic growth mediates the tourism sector on people's welfare, (6) the influence of financial performance mediates the tourism sector on people's welfare, (7) the influence of economic growth and financial performance mediates the influence of the tourism sector on people's welfare. This type of research is quantitative. The subject of this research is the Government of Bulukumba Regency. The population of this study is the tourism sector, economic growth, financial performance, community welfare. The sample of this research is data from 2010-2020. Data analysis in this study was using the partial Least Square (PLS) model. The results showed that (1) the tourism sector had an effect on financial performance, (2) the tourism sector had no effect on economic growth, (3) economic growth had no effect on financial performance, (4) financial performance had an effect on people's welfare, (5) growth the economy cannot mediate the tourism sector on financial performance, (6) financial performance is able to mediate the tourism sector on people's welfare, (7) economic growth and financial performance are unable to mediate economic growth on people's welfare.